0
$\begingroup$

Need guidance on this proof by mathematical induction. I am new to this type of math and don't know how exactly to get started.

$$ 1^3 + 2^3 + 3^3 + \ldots + n^3 = \left[\frac{n(n+1)}{2}\right]^2 $$

$\endgroup$
  • $\begingroup$ What's PMI? What does "n3" mean? ... $\endgroup$ – DonAntonio Mar 25 '13 at 23:31
  • $\begingroup$ I'm assuming it's "proof by mathematical induction" and the question is asking about the result for the sum of the first $n$ cubes. $\endgroup$ – Stahl Mar 25 '13 at 23:32
  • 1
    $\begingroup$ Show that the formula is true for $n=1$. assume the formula is true for $n = k$. using that information, show that the formula holds true for $k + 1$. These sorts of proofs by induction are very straightforward, but only if you know how an induction proof works. $\endgroup$ – Tyler Mar 25 '13 at 23:35
  • $\begingroup$ Possible duplicate $\endgroup$ – Adi Dani Mar 26 '13 at 0:03
  • $\begingroup$ @AdiDani huh? what does that mean $\endgroup$ – JustaBreitGuy Mar 26 '13 at 0:08
1
$\begingroup$

To prove something via mathematical induction, first you need to identify the mathematical statement $P(n)$ that you're trying to verify. By mathematical statement, I mean something like "let $P(n)$ be the statement $n = n$." When you prove something with induction, you are trying to show that $P(n)$ is true for all $n\in\Bbb{N}$. See if you can identify the statement relevant to your problem first, but if you get stuck, you can hover your mouse over the area below to see it.

Let $P(n)$ be the statement: $\sum_{k = 1}^n k^3 = \left[\frac{n(n+1)}{2}\right]^2$

The next step is showing that $P(1)$ is true; i.e. that the statement holds for $n = 1$. This should be easy.

$P(1):$ $\sum_{k = 1}^1 k^3 = 1^3 = \left(\frac{1\cdot2}{2}\right)^2 = 1^2 = 1$ is true.

After that, assume $P(n)$ is true. Then you want to use that assumption to show that $P(n+1)$ is true (you should be able to break the statement up into what you already know ($P(n)$) and then perform algebraic manipulation to show that $P(n+1)$ is true). Once you do that, the principle of mathematical induction tells you that $P(n)$ is true for all $n$, as $P(1)$ is true and $P(n)\implies P(n+1)$. I've left the last part for you to figure out yourself, as it's the bulk of the proof.

Hint: Start with $P(n)\implies \sum_{k = 1}^n k^3 = \left[\frac{n(n+1)}{2}\right]^2$, so $\sum_{k = 1}^{n+1} k^3 = \left[\frac{n(n+1)}{2}\right]^2 + \left(n+1\right)^3$.

$\endgroup$
1
$\begingroup$

This is easy for $n = 1$. Assume it is true for $n$. Then $$\sum_{k=1}^{n+1} k^3 = (n + 1)^3 + \sum_{k=1}^n k^3.$$ Now invoke the induction hypothesis to get $$\sum_{k=1}^{n+1} k^3 = (n + 1)^3 + {n^2(n + 1)^2\over 4}.$$ Now wrangle the right hand side until you get $${(n+1)^2(n+2)^2\over 4}.$$

$\endgroup$
1
$\begingroup$

Leaving out the trivial case, assume true for $n$, let's prove for $n+1$:

$$\begin{align*} 1^3+ \dots + n^3+(n+1)^3 &= \left(\frac{n(n+1)}{2}\right)^2+(n+1)^3 \\ & = (n+1)^2\left(\frac{n^2}{4}+n+1\right) \\ & = \left(\frac{(n+1)}{2}\right)^2(n^2+4n+4)\\ & = \left(\frac{(n+1)(n+2)}{2}\right)^2 \end{align*}$$

$\endgroup$
  • $\begingroup$ @leo what do I do about the n+2? isnt it supposed to equal [n(n+1)/2]^2 $\endgroup$ – JustaBreitGuy Mar 26 '13 at 0:41
  • $\begingroup$ No, the proof is for the (n+1) case so it is one more than the previous case. $\endgroup$ – JB King Mar 26 '13 at 0:46
  • 1
    $\begingroup$ @JB King $$1^3+2^3+\ldots+n^3+(n+1)^3+(n+2)^3=\left[\frac{(n+2)(n+3)}{2}\right]^2$$ $\endgroup$ – leo Mar 26 '13 at 1:37
1
$\begingroup$

Inductive proofs of sums like yours are easily tackled using a very simple general method known as telescopy - see the trivial inductive proof here, of the following fundamental

Theorem $\rm \displaystyle\ \ \sum_{i\,=\,0}^n\, f(i)\, =\, g(n)\iff f(0) = g(0)\ {\rm\ and\ }\ f(n) \,=\, g(n)-g(n\!-\!1)\:\ $ for $\rm\,n \ge 1.$

In your case we have $\rm\ f(n) \,=\, n^3,\,\ \ g(n) \,=\, (n(n+1)/2)^2\ $ so $\rm\ f(0) = g(0)\ $ and

$$\rm g(n)\!-\!g(n\!-\!1)\, =\, \dfrac{(n(n\!+\!1))^2}4 - \dfrac{((n\!-\!1)n)^2}4 =\, \dfrac{n^2\,\big((n\!+\!1)^2\!-(n\!-\!1)^2\big)}{4} =\, n^3\!= f(n)\ \ \ {\bf QED}$$

You can find many more examples of telescopy and related results in other answers here.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.